Computational Prediction of Flavonoid Metabolites and their Inflammatory Effects on HT29-MTX Human Intestinal Epithelial Cells. - Fitzsimmons, Ari. (Tufts University. Tisch Library., 2019)
Many studies have been published indicating that the complex ecosystem that is the gut microbiota plays an important role in human health, including in obesity risk, inflammation, and antioxidant production. However, the gut species makeup varies greatly among individuals, and not everyone receives that same benefits. Therefore, it is important to identify not only what metabolites are providing these beneficial effects, but also which organisms produce them. Flavonoids, a class of polyphenolic compounds found in high abundance in many plant sources, have gained attention recently for exhibiting anti-inflammatory, antioxidant, and anti-cancer properties. In this study, we computationally predicted metabolic derivatives of flavonoids from an expanded spinach model based on a mouse cecal microbiota model. A selection of these predicted flavonoid derivatives were tested for anti-inflammatory properties on HT29-MTX cells. Results were found to be contradictory to previously published data. Predicted derivatives were found to have a pro-inflammatory effect on HT29-MTX cells. Further studies need to be conducted to confirm that these results are not exclusive to HT29-MTX cells.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Kyongbum Lee.; Committee: Soha Hassoun, and Emmanuel Tzanakakis.; Keyword: Bioengineering.